2022
DOI: 10.1039/d1en01067k
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics analysis reveals size-dependent toxicity and vascular endothelial cell injury induced by microplastic exposurein vivoandin vitro

Abstract: Microplastics (MPs) pollution has gained increasing attention recently. Fewer studies have examined the effects of these small items on the vascular system. The aim of this work was to precisely...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…MNPs cause endothelial cell dysfunction by diminishing mitochondrial function and increasing pro-inflammatory cytokines, thereby triggering apoptosis [ 64 ]. This study also revealed differences in gene expression and metabolite levels between MNP-treated endothelial cells.…”
Section: Toxicities Of Micro- and Nanoplastics On Mitochondriamentioning
confidence: 99%
“…MNPs cause endothelial cell dysfunction by diminishing mitochondrial function and increasing pro-inflammatory cytokines, thereby triggering apoptosis [ 64 ]. This study also revealed differences in gene expression and metabolite levels between MNP-treated endothelial cells.…”
Section: Toxicities Of Micro- and Nanoplastics On Mitochondriamentioning
confidence: 99%
“…T A B L E 2 Summary of the damage of cell membrane and organelle caused by MPs. A number of studies have also reported that PS MPs significantly change mitochondrial membrane permeability (Salimi et al, 2022;Shen et al, 2022;Wu et al, 2019;Zhang, Shi, et al, 2022;Zhang, Wang, et al, 2022), and the mechanisms may include: (1) excessive ROS in the cytoplasm mediating the opening of Na/K transmembrane channels on the mitochondrial membrane, which aggravates disordered mitochondrial membrane potential (Salimi et al, 2022);…”
Section: The Mitochondriamentioning
confidence: 99%
“…PS exposure reduce HO‐1 activity to promote oxidative stress in cells (Chen et al, 2022). A number of studies have also reported that PS MPs significantly change mitochondrial membrane permeability (Salimi et al, 2022; Shen et al, 2022; Wu et al, 2019; Zhang, Shi, et al, 2022; Zhang, Wang, et al, 2022), and the mechanisms may include: (1) excessive ROS in the cytoplasm mediating the opening of Na/K transmembrane channels on the mitochondrial membrane, which aggravates disordered mitochondrial membrane potential (Salimi et al, 2022); (2) MPs affect the membrane structure by destroying the mitochondrial electron transport chain (ETC), resulting in a decrease in mitochondrial membrane potential and mitochondrial depolarization (Zhang, Wang, et al, 2022). MPs affect mitochondrial function by changing mitochondrial membrane potential.…”
Section: Damage Of Cell Membrane and Organelle Caused By Mpsmentioning
confidence: 99%
“…In HUVEC cells, cytotoxicity was observed after exposure to 50 nm PS particles with a concentration of 50 µg/mL [165][166][167] . In addition, all sizes (20-10000 nm, 1000 µg/mL) resulted in apoptosis, with higher apoptosis rates observed in cells treated with smaller PS particles 167 . Furthermore, exposure to 20, 100 and 10000 nm (1000 µg/mL) PS particles resulted in lactate dehydrogenase (LDH) leakage.…”
Section: Toxicitymentioning
confidence: 99%
“…Also, placental accumulation and potential toxic effects could be investigated by using various markers of toxicity and multi-omics approaches, such as RNA sequencing and metabolomic profiling 167,188 . However, taking into account a large number of possible experimental conditions (the multitude of MNP polymer types, shapes and sizes), the most important consideration for tissue explant cultures and placental perfusion studies is the low throughput of these methods: they are laborious, time-consuming, and, morphological and functional characterization of these fragile tissues has to be performed at different time points to ensure robust results.…”
Section: Choosing the Right Human Placental Modelmentioning
confidence: 99%